2019
DOI: 10.1590/0034-737x201966060008
|View full text |Cite
|
Sign up to set email alerts
|

Silicate fertilization in non-conventional vegetables in the southern region of Minas Gerais in Brazil

Abstract: Considering that the beneficial effects of silicon on human health and it´s accumulation in plants are little explored, studies of mineral nutrition in non-conventional vegetables are extremely relevant. Thus, the objective of this work was to identify non-conventional vegetables responsive to silica fertilization and evaluate the effect of fertilization on the content and accumulation of Si and macronutrients in these plants. The experiment followed a 4 x 5 factorial design, with four species of non-conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…Furthermore, Si reversed the deleterious effects of wastewater, stimulated plant growth which increased the uptake of N, P and K due to higher internal demand. Oliveira et al, demonstrated that Si could increase the uptake of N, P and K in non-conventional vegetables [41]. Li et al, also reported an increase in P concentration in plants with the application of Si [42].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Si reversed the deleterious effects of wastewater, stimulated plant growth which increased the uptake of N, P and K due to higher internal demand. Oliveira et al, demonstrated that Si could increase the uptake of N, P and K in non-conventional vegetables [41]. Li et al, also reported an increase in P concentration in plants with the application of Si [42].…”
Section: Discussionmentioning
confidence: 99%
“…The application of 50 mg L -1 SiO 2 at the lowest moisture level increased the concentration of Si in the root by 53.3% compared to the treatment without Si. Silicon fertilization can increase the concentration of the element in plant tissues, but very high doses can generate an antagonistic effect (Oliveira, et al, 2019). The contents of Si in plant tissues can vary depending on the applied dose (Oliveira et al, 2019), the genetics and the absorption mechanisms of each plant (Hodson, White, Mead, Broadley, 2005).…”
Section: Silicon (Si) Concentrationmentioning
confidence: 99%
“…Silicon fertilization can increase the concentration of the element in plant tissues, but very high doses can generate an antagonistic effect (Oliveira, et al, 2019). The contents of Si in plant tissues can vary depending on the applied dose (Oliveira et al, 2019), the genetics and the absorption mechanisms of each plant (Hodson, White, Mead, Broadley, 2005). The distribution of Si in the shoots of the plant is regulated by several factors among which is transpiration (Ma and Yamaji, 2006).…”
Section: Silicon (Si) Concentrationmentioning
confidence: 99%
“…Among the leafy vegetables, Rumex acetosa L., Stachys byzantina K. Koch. and Lactuca canadensis L. have been gaining space and arousing the interest of producers and the consumer market (Silva et al 2017, Silva et al 2018a, Oliveira et al 2019, Oliveira et al 2020.…”
Section: Palavras-chavementioning
confidence: 99%